TRANSFORMATION OF DOMESTIC TOURISM IN UKRAINE DURING THE WAR: FORECASTING PROSPECTIVE TYPES OF TOURISM - Чорна, Наталія; Антонюк, Катерина (SWorldJournal, 2024)
The article discusses popular types of domestic tourism in conditions of military aggression. Determining the prospects for the development of tourism in the future, it is worth taking into account the transformation of types of tourism in the post-war p